2018
DOI: 10.1021/acs.jafc.8b06114
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations and Dietary Exposure to Organophosphate Esters in Foodstuffs from Albany, New York, United States

Abstract: Organophosphate esters (OPEs) are ubiquitous contaminants in the environment, but little is known about their occurrence in foodstuffs, an important source of human exposure. In this study, 15 OPEs were measured in foodstuffs and food-packing materials collected from local markets in Albany, New York, United States, for the first time. Among the foodstuffs analyzed, median concentrations of ∑OPEs (sum of 15 OPEs) in meat (6.76 ng/g wet weight; ww) and fish/seafood (7.11 ng/g ww) were higher than those in other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(74 citation statements)
references
References 51 publications
(115 reference statements)
5
62
0
Order By: Relevance
“…Our measured median concentrations of PFRs (Figure 3) were comparable with the levels detected in edible insects and insect-based food for human consumption from our previous study (Poma et al 2017a). In the same way, the median contamination with PFRs and plasticizers in insect samples was similar between the EU, PRC, and JPN/SK, always dominated by aromatic-PFRs (see Figure S2) and DEHP, and was comparable with median levels measured in foodstuffs of animal origin from worldwide studies (Cariou et al 2016;Cheng et al 2016;Ding et al 2018;He et al 2015;Poma et al 2017bPoma et al , 2018Van Holderbeke et al 2014;Wang and Kannan 2018;Yang et al 2018). For these two groups of compounds, the contamination in the insects could have occurred during production [e.g., from the rearing substrate, from the polyvinyl chloride (PVC) gloves used by workers during insect rearing and handling, etc.…”
Section: Discussionsupporting
confidence: 74%
“…Our measured median concentrations of PFRs (Figure 3) were comparable with the levels detected in edible insects and insect-based food for human consumption from our previous study (Poma et al 2017a). In the same way, the median contamination with PFRs and plasticizers in insect samples was similar between the EU, PRC, and JPN/SK, always dominated by aromatic-PFRs (see Figure S2) and DEHP, and was comparable with median levels measured in foodstuffs of animal origin from worldwide studies (Cariou et al 2016;Cheng et al 2016;Ding et al 2018;He et al 2015;Poma et al 2017bPoma et al , 2018Van Holderbeke et al 2014;Wang and Kannan 2018;Yang et al 2018). For these two groups of compounds, the contamination in the insects could have occurred during production [e.g., from the rearing substrate, from the polyvinyl chloride (PVC) gloves used by workers during insect rearing and handling, etc.…”
Section: Discussionsupporting
confidence: 74%
“…While little is known about dietary predictors of urinary OPE concentrations, findings from two small studies suggest that intake of fresh foods, certain vegetables, citrus fruit, eggs, or meats may be associated with lower concentrations of several OPE metabolites ( Romano et al 2017 ; Thomas et al 2017 ). OPEs have been measured in food packaging materials ( Wang and Kannan 2018 ) and food samples including seafood, meat, dairy, fats, oils, grains, rice, cheese, cereals, pastries, sugar/sweets, vegetables, and beverages ( Ding et al 2018 ; He et al 2018b ; Poma et al 2018 , 2017 ; Wang and Kannan 2018 ; Zhang et al, 2016b ). Notably, Poma et al ( Poma et al 2018 ) reported that 89% of the processed foods assessed contained OPEs as compared with only 11% of non-processed foods.…”
Section: Discussionmentioning
confidence: 99%
“…2017 ; Li et al. 2019b ; Wang and Kannan 2018 ; Wang et al. 2019 ), either owing to its spontaneous/microorganism production from known APEs ( Fu et al.…”
Section: Introductionmentioning
confidence: 99%